Biocompatibility of intracortical microelectrodes: current status and future prospects - Marin, Cristina; Fernandez, Eduardo (Frontiers in Neuroengineering, 2010)
Rehabilitation of sensory and/or motor functions in patients with neurological diseases is more and more dealing with artificial electrical stimulation and recording from populations of neurons using biocompatible chronic implants. As more and more patients have benefited from these approaches, the interest in neural interfaces has grown significantly. However an important problem reported with all available microelectrodes to date is long-term viability and biocompatibility. Therefore it is essential to understand the signals that lead to neuroglial activation and create a targeted intervention to control the response, reduce the adverse nature of the reactions and maintain an ideal environment for the brain-electrode interface. We discuss some of the exciting opportunities and challenges that lie in this intersection of neuroscience research, bioengineering, neurology and biomaterials.